Biology's beginnings - Hakim, Joy (Hakim, Joy. Discovering life's story, 2023)
"This first of a four-part MITeen series charts the evolution of life science up to the late 1800s, when the origins of the virus was discovered by a baffled Dutch biologist who found a tiny infectious particle destroying tobacco crops"--